2007
DOI: 10.1073/pnas.0608498104
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of complex protein dynamics in human thioredoxin

Abstract: We report our direct study of complex protein dynamics in human thioredoxin by dissecting into elementary processes and determining their relevant time scales. By combining site-directed mutagenesis with femtosecond spectroscopy, we have distinguished four partly time-overlapped dynamical processes at the active site of thioredoxin. Using intrinsic tryptophan as a molecular probe and from mutation studies, we ascertained the negligible contribution to solvation by protein sidechains and observed that the hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 56 publications
9
47
0
Order By: Relevance
“…Long relaxation t imes in our experiments are also confi rmed by results fro m recent wo rk using femtosecond-resol ved fluorescence spectroscopy and the other techniques to break down the co mplex p rotein dynamics into four elementary processes and determine their relevant time scales [32,42]. A mong these processes the authors determined "a robust dynamical process in 95-114 ps" that is very close to the relaxat ion time in our experiments with Bru ker spectrometer, and also much longer quenching dynamic processes with time scales of 275-615 ps at a hydrogen bond distance, which can give local fluctuations with v ibrations spectral line width of 0.12-0.054 cm -1 .…”
Section: Simulation and Discussionsupporting
confidence: 48%
“…Long relaxation t imes in our experiments are also confi rmed by results fro m recent wo rk using femtosecond-resol ved fluorescence spectroscopy and the other techniques to break down the co mplex p rotein dynamics into four elementary processes and determine their relevant time scales [32,42]. A mong these processes the authors determined "a robust dynamical process in 95-114 ps" that is very close to the relaxat ion time in our experiments with Bru ker spectrometer, and also much longer quenching dynamic processes with time scales of 275-615 ps at a hydrogen bond distance, which can give local fluctuations with v ibrations spectral line width of 0.12-0.054 cm -1 .…”
Section: Simulation and Discussionsupporting
confidence: 48%
“…Under this perturbation, the response, in principle, can result from both the surrounding water molecules and the local protein backbone and side chains. However, our recent solvation studies on the enzymes Staphylococcus nuclease (25) and human thioredoxin (26) by systematic mutations of charged and polar residues around the tryptophan probe indicated that the response is dominantly from surfacewater motions and the contributions from the proteins are minor. With the massive data presented here, we are able to examine the global surface hydration dynamics and their relationships to protein properties and its fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…These processes represent the dynamic exchange of hydration layer water with outside bulk water via thermal fluctuations. Femtosecond-resolved spectroscopic studies of protein solvation (19)(20)(21)(22)(23)(24)(25)(26) recently have shown the dynamics of surface hydration on picosecond time scales with a biphasic distribution. We attributed the first ultrafast solvation to water local relaxation and the second longer-time dynamics to coupled water-protein fluctuations (25,27).…”
mentioning
confidence: 99%
“…These dynamics involve local constrained protein and trapped-water motions within angstrom distance and occur on ultrafast time scales (6,7,10,11). Typically, extrinsic dye molecules or synthetic amino acids were used as local optical probes to label function sites, and the local relaxations were observed, ranging from femtoseconds to nanoseconds (5,(12)(13)(14).…”
mentioning
confidence: 99%
“…function-site solvation | ultrafast dynamics | spectral tuning | protein rigidity and flexibility | femtosecond-resolved emission spectra D ynamic solvation in binding and active sites plays a critical role in protein recognition and enzyme reaction, and such local motions optimize spatial configurations and minimize energetic pathways (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). These dynamics involve local constrained protein and trapped-water motions within angstrom distance and occur on ultrafast time scales (6,7,10,11).…”
mentioning
confidence: 99%